Statins Alleviate Tumor Hypoxia in Prostate Cancer Models by Decreasing Oxygen Consumption: An Opportunity for Radiosensitization? - Donatienne d’Hose; Lionel Mignion; Loïc Hamelin; Pierre Sonveaux; Bénédicte F. Jordan; Bernard Gallez (Biomolecules, 2022)
Background: Because statins were found to decrease the oxygen consumption rate (OCR) of a variety of normal cells, our hypothesis was that statins may also decrease the OCR of cancer cells, alleviate tumor hypoxia and radiosensitize tumors. Methods: OCR was assessed using the Seahorse XF96 technology and EPR respirometry in PC-3 prostate cancer cells. Mitochondrial superoxide production was measured by EPR with mitoTEMPO-H as a sensing probe. Tumor pO2 was measured in vivo using low-frequency EPR oximetry to define the optimal window of reoxygenation, the time at which tumors were irradiated with a single 6 Gy dose with a Cesium-137 irradiator. Results: 24-h exposure to simvastatin and fluvastatin significantly decreased the OCR of PC-3 cancer cells. An increase in mitochondrial superoxide levels was also observed after fluvastatin exposure. The PC-3 prostate cancer model was found highly hypoxic at the basal level. When mice were treated with simvastatin or fluvastatin (daily injection of 20 mg/kg), tumor oxygenation increased 48 and 72 h after initiation of the treatment. However, despite reoxygenation, simvastatin did not sensitize the PC-3 tumor model to RT. Conclusions: exposure to statins affect tumor metabolism and tumor oxygenation, however, with limited impact on tumor growth with or without irradiation.